Finding joy. Series 2 [videorecording (DVD)] - Butler, John (Director); Huberman, Amy; Huberman, Amy; Reid, Paul (Actor); James-Scott, Hannah (Acorn Media, 2021)
When a television reporter begins her own new channel, she goes back to high school in hopes of bringing in more subscribers.